Pengaruh Advertising dan Online Customer Review Terhadap Keputusan Pembelian Moisturizer Skintific di TikTok Shop - Hilman Rismanto; Amelia Amelia; Sani Febriani; Dhea Octavia; Djian Rafika (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the effect of advertising and online customer reviews on purchase decisions of Skintific moisturizer products on TikTok Shop. A quantitative approach was employed using a survey method involving 94 respondents who had purchased the product through TikTok Shop. Data were collected through structured questionnaires and analyzed using multiple linear regression. The results indicate that advertising has no significant effect on purchase decisions. Similarly, online customer reviews do not significantly influence purchase decisions. Simultaneous testing also reveals that advertising and online customer reviews jointly have no significant effect on purchase decisions. These findings suggest that purchase decisions for skincare products in social commerce platforms are not solely determined by advertising exposure and customer reviews, but are influenced by other factors beyond the proposed model. This study provides empirical evidence that enriches the literature on digital marketing and social commerce, particularly in the context of TikTok Shop.